2005
DOI: 10.1042/bj20041709
|View full text |Cite
|
Sign up to set email alerts
|

Identification of adipocyte adhesion molecule (ACAM), a novel CTX gene family, implicated in adipocyte maturation and development of obesity

Abstract: Few cell adhesion molecules have been reported to be expressed in mature adipocytes, and the significance of cell adhesion process in adipocyte biology is also unknown. In the present study, we identified ACAM (adipocyte adhesion molecule), a novel homologue of the CTX (cortical thymocyte marker in Xenopus) gene family. ACAM cDNA was isolated during PCR-based cDNA subtraction, and its mRNA was shown to be up-regulated in WATs (white adipose tissues) of OLETF (Otsuka Long-Evans Tokushima fatty) rats, an animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 45 publications
0
48
0
Order By: Relevance
“…The second one is terminal differentiation, in which the preadipocytes become mature adipocytes (Rosen and MacDougald, 2006). A previous study suggested that an adipocyte adhesion molecule (ACAM), a 45 kDa protein expressed on adipocytes is involved in adipocyte maturation (Eguchi et al, 2005). In our study, we showed that the adipocyte differentiation in Ncam -/-MSCs is impaired because there was reduced induction of the adipocyte differentiation markers PPARg and P2, and less lipid accumulation.…”
Section: Discussionmentioning
confidence: 52%
“…The second one is terminal differentiation, in which the preadipocytes become mature adipocytes (Rosen and MacDougald, 2006). A previous study suggested that an adipocyte adhesion molecule (ACAM), a 45 kDa protein expressed on adipocytes is involved in adipocyte maturation (Eguchi et al, 2005). In our study, we showed that the adipocyte differentiation in Ncam -/-MSCs is impaired because there was reduced induction of the adipocyte differentiation markers PPARg and P2, and less lipid accumulation.…”
Section: Discussionmentioning
confidence: 52%
“…These are three membrane-associated guanylate kinases (MPP1, MPP7, and SAP102), members of a family of proteins known to be involved in cell-to-cell adhesion (48), and the adipocyte adhesion protein, a transmembrane protein that has been shown to participate in cell aggregation (49). Thus, it is possible that insulin treatment may alter the adipocyte/adipocyte interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Also, it is detectable on the plasma membrane of mature adipocytes and facilitates their cell-cell adhesion. 13 In this study, during early adipogenic differentiation of MSCs, ACAM was initially invisible and then gradually detectable on cell membrane (Fig. 6A-D).…”
Section: Discussionmentioning
confidence: 99%
“…11 Antibodies raised in rabbits against the ACAM were kindly donated for the study by Dr. Jun Wada from Okayama University, Japan. 13 Effects of Tb 4 on In Vitro Differentiation of BM-MSCs Osteogenic, chondrogenic, and adipogenic differentiation of MSCs was induced, as previously described. 14 For all these differentiation studies, 1 mg/mL Tb 4 was added to induction medium once every 3 days along with each medium change.…”
Section: Methodsmentioning
confidence: 99%